Dynamic chromatin: ATP-dependent chromatin remodeling machines - Cairns, Bradley (Henry Stewart Talks, 2007)
ATP-dependent chromatin remodeling complexes, ATP hydrolysis and nucleosome dynamics, Mechanistic action, Cellular function
Archived at 2022/04/13